Pengaruh Literasi Keuangan, Gaya Hidup, dan Perilaku Konsumtif terhadap Intensitas Penggunaan QRIS pada Mahasiswa FEB Unsoed - Shandy Aulia Hartono; Cahyani Ade Saputri; Ratu Atut Falaqiah; Dian Isnawati; Aldila Krisnaresanti (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of digital payment systems in Indonesia has encouraged students to increasingly use Quick Response Code Indonesian Standard (QRIS) as a practical and efficient transaction method. This study aims to analyze the influence of financial literacy, lifestyle, and consumptive behavior on the intensity of QRIS usage among students of the Faculty of Economics and Business, Universitas Jenderal Soedirman. This research used a quantitative approach with a survey method through questionnaires distributed to respondents. The sampling technique applied was convenience sampling with a total sample of 70 students. Data analysis was conducted using multiple linear regression analysis. The results showed that partially, financial literacy, lifestyle, and consumptive behavior did not have a significant effect on the intensity of QRIS usage. However, simultaneously, the three variables jointly influenced the intensity of QRIS usage among students. These findings indicate that the use of QRIS is influenced not only by individual factors but also by the combination of financial understanding, lifestyle patterns, and consumptive tendencies. Therefore, increasing financial literacy and wise digital transaction behavior are important in encouraging more effective and responsible use of QRIS among students.